The 1972 Munich Olympics and the making of modern Germany - Schiller, Kay (Weimar and now, 2010)
The 1972 Munich Olympics--remembered almost exclusively for the devastating terrorist attack on the Israeli team--were intended to showcase the New Germany and replace lingering memories of the Third Reich. That hope was all but obliterated in the early hours of September 5, when gun-wielding Palestinians murdered 11 members of the Israeli team. In the first cultural and political history of the Munich Olympics, Kay Schiller and Christopher Young set these Games into both the context of 1972 and the history of the modern Olympiad. Delving into newly available documents, Schiller and Young chroni.